ANALISIS BIAYA UNTUK PEMILIHAN SUMBER DAYA LISTRIK UTAMA RUMAH POMPA GREGES - Yudiono Yudiono; Umboro Lasminto; Vita Ratnasari (Institut Teknologi Sepuluh Nopember, 2018)
The central government through the Directorate of Environmental Sanitation Development (PPLP) of the Directorate General of Human Settlements of the Ministry of Public Works and Public Housing participated in the implementation of drainage of Surabaya by providing assistance for the construction of Greges pump house. The pump house Greges as one of the pump house located in Surabaya, is one of the drainage system controllers around Bozem Morokrembangan area especially the flow of water along the Greges channel which is also an outlet for several channels. In the aid of the pump house choose to use Genset as the main power source (SDL). While the Government of Surabaya always wants the use of SDL from PLN. The purpose of this study was to analyze the use of SDL to meet the needs of the Greges Pump House by performing the cost analysis required for the Greges pump house for the use of Genset and PLN power sources, and determining the better SDL selection that would be used to meet the needs of the Greges pump house. Based on the analysis of costs, the use of generators is better than PLN in the investment cost analysis. Based on PLN operational cost analysis is better than generator. In the first year period the total cost for the use of PLN is Rp. 5.102.223.905 greater than the generator Rp. 4.789.084.970,16,, in the second year the cost of using PLN approaches the generator cost, and on the third and so the use of generator is higher than the PLN.